Servicio al cliente en el mercado 4 de Mayo en la ciudad de Babahoyo - Morán Tomalá, Jomara Elizabeth (2021)
The present case study consists of analyzing the customer service, which the May 4 Market of the city of Babahoyo has, in order to know the fundamental problems that harm the entity internally and that influence the process of attention to consumers who come to the store to make their purchases of basic necessities. The information presented in the current document has been validated, by the main actors involved in the aforementioned place, by means of technical tools such as the interview and survey of each of the intermediaries. Through the application of the deductive method together with a descriptive-documentary research, the data and information provided in this case study, aims to make society aware, from a professional and administrative point of view, about the various Factors that can influence the optimal customer service process in one of the best-known supply centers in the city of Babahoyo, such as Mercado 4 de Mayo.